Directed Reading Thinking Activity Strategy for Narrative Text Comprehension in Madrasah Ibtidaiyah Students - Ayu Dwi Asih; Syafrimen Syafril; Chairul Amriyah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze the application of the Directed Reading Thinking Activity strategy in improving narrative text comprehension among Madrasah Ibtidaiyah students through a systematic literature review. The research followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol to identify, screen, and evaluate relevant studies from databases such as Google Scholar, Scopus, and Semantic Scholar using keywords including Directed Reading Thinking Activity, reading comprehension, narrative text, elementary students, and Madrasah Ibtidaiyah. A total of 28 articles met the inclusion criteria and were analyzed. The findings show that the Directed Reading Thinking Activity strategy has a positive impact on students’ reading comprehension, particularly in understanding narrative structure and content. This strategy encourages active student engagement through prediction, critical reading, and verification activities. Furthermore, the Directed Reading Thinking Activity strategy contributes to the development of critical thinking skills and student participation in reading instruction. Therefore, the Directed Reading Thinking Activity strategy can be considered an effective pedagogical approach to enhance reading comprehension in Madrasah Ibtidaiyah.